Integrated and holistic knowledge map of phase change materials for pavement: A scientometric analysis and bibliometric review - Jiasheng Dai; Feng Ma; Zhen Fu; Chen Li; Yingjie Hou; Yalu Wen; Yanzhe Zou; Dongdong Yuan; Wenhao Dong; Ke Shi (Journal of Traffic and Transportation Engineering (English ed. Online))
Elevated pavement temperatures contribute to the urban heat island effect and pose a risk of thermal damage to pavement. Thus, regulating pavement temperature is paramount to ensure its longevity, enhance traffic safety, and preserve the environment. Phase change materials (PCMs) with the latent heat characteristic can store and release thermal energy via phase transitions. PCMs can effectively control pavement structure temperatures within a relatively narrow range, mitigating thermal stress on asphalt pavements. This research aims to explore the current status and emerging trends in PCM integrated pavement engineering (PCMIPE) using the CiteSpace visual analysis tool. Relevant publications were systematically curated from the Web of Science core database, spanning 2011 to 2023. Subsequently, the co-authorships network maps (country, institution, author), co-cited network maps (co-cited journals, authors, and references), and keyword co-occurrence network maps were constructed to analyze the principal contributions in the PCMIPE field comprehensively. This analysis provides an understanding of the field's strengths, research domains, and knowledge structure and identifies current research focal points and emerging frontiers. The findings reveal that research within the PCMIPE field is still in its early stages, with a predominant emphasis on material design and performance assessment. Additionally, future research is anticipated to expand into economic analyses and exploration of environmental effects when integrating PCMs into pavement engineering. Furthermore, there is an emerging interest in investigating the synergy of PCMs with other functional pavement technologies. These results underscore the potential of the PCMIPE field and emphasize the importance of future research endeavors.